Spatial distribution of paddy field’s heavy metals diversity contamination in Samarinda using remote sensing imagery - NURUL PUSPITA PALUPI; ESTI HANDAYANI HARDI; FAHRUNSYAH FAHRUNSYAH; DWI ERMAWATI RAHAYU; RUDY AGUNG NUGROHO; SURYA DARMA; SURIA DARMA IDRIS (Society for Indonesian Biodiversity, 2023)
Abstract. Palupi NP, Hardi EH, Fahrunsyah, Rahayu DE, Nugroho RA, Darma S, Idris SD. 2023. Spatial distribution of paddy field’s heavy metals diversity contamination in Samarinda using remote sensing imagery. Biodiversitas 24: 6743-6752. The adverse effects of heavy metal contamination on rice fields posing a significant threat to food safety. This study, conducted from May to July 2023 in Samarinda East Kalimantan, Indonesia, aims to determine the distribution of active rice fields and heavy metal contamination through Kriging's interpolation method. Aerial photographic interpretations, facilitated by ArcGIS 10.4, were performed with 144 sample points within 4 Districts. The content of heavy metals was assessed by Atomic Absorption Spectroscopy at specific wavelengths: 248.3 nm for Fe, 228.8 nm for Pb, 283.3 nm for Cd, 357.9 nm for Cr, 279.5 nm for Mn, 213.9 nm for Zn, and 324.7 nm for Cu, following guidelines of SNI 8910:2021. The research showed that existing rice fields were concentrated in North Samarinda District (380,416 ha), Loa Janan Ilir District (210,133 ha), Sambutan District (404,682 ha), and Palaran District (188,617 ha) with Fe content ranged from 4.976,45 ppm to 16.800,485 ppm, exceeding the critical Fe limit in soil of 500 ppm set by SNI. Mn content ranged from 22.65 ppm to 564.88 ppm, surpassing the critical soil threshold of 0.15 ppm for Mn according to SNI. Cu content varied from 3.32 ppm to 121.75 ppm, exceeding critical Cu limit of 0.04 ppm. Zn content ranged from 8.61 ppm to 223.12 ppm, surpassing the critical limit of Zn's pollution in the soil (0.06 ppm). Pb content ranged from 10.72 ppm to 32,84 ppm, categorized as intermediate compared to the threshold of 0.07 ppm for Pb in soil. Cd content ranged from 0.04 ppm to 0.739 ppm, exceeding the critical limit of 0.01 ppm set by SNI. Cr content was detected to be less than 0.032 ppm, falling into a very low category, with the critical limit for Cr content in soil set at 0.5 ppm according to SNI.